THE POTENTIAL EFFECT OF TWO CYANOBACTERIAL SPECIES; ANABAENA SPHAERICA AND OSCILLATORIA AGARDHII AGAINST GRAIN STORAGE FUNGI - Haggag, Wafaa; El-Aty, Azza M. Abd; Mohamed, Amal A. (European Scientific Journal, ESJ, 2014)
Cyanobacterial secondary metabolites have a diverse antagonistic activity that lead to disintegration of microbial growth. The present study was undertaken to explore the inhibitory effect of three different solvents extracts (methanol, acetone and water) of two cyanobacteria species: Oscillatoria agardhii and Anabaena sphaerica extracts against grain storage fungi. In vitro fungal growth, mycotoxins production of grain storage fungi (Fusarium equiseti; F. moniliforme; F. solani; F. proliferatum , F. graminearum; Penicillium digitatum; Aspergillus terreus; Aspergillus niger; Aspergillus flavus; Aspergillus oryza; Alternaria alternate and Alternaria triticina) were significantly(p<0.01) inhibited by cyanobacterial extracts. HPLC analysis revealed that compelate reduction of Aflatoxin B1, Zearalenone and Fumonisin B1 with acetone extract of Oscillatoria agardhii and minimum concentration (0.3Î¼g/L) was found with Ochratoxin A. Acetone extracts of both cyanobacteria species have potential for the suppression of all grain storage fungi and increased seeds germination of maize, wheat, barley and rice. It was also observed that when wheat seeds treated with water extract for one hour soaking, significant (p<0.01) increased in seed germination and reduced the frequency of seeds storage fungi during 180 days was also observed. These results statements be a necessary (or) recommended that the both species of Cyanobacterial having a potential capacity as a source of antifungal activity, which makes them interesting for screening for natural and highly bioactive secondary metabolites products and it may leads to development of new pharmaceutical agents.